2003
DOI: 10.1086/367842
|View full text |Cite
|
Sign up to set email alerts
|

Gram Stain, Culture, and Histopathological Examination Findings for Heart Valves Removed because of Infective Endocarditis

Abstract: Retrospective chart review was undertaken for 480 patients who underwent a total of 506 valve replacements or repair procedures for infective endocarditis. The influence of preoperative antimicrobial treatment on culture, Gram stain, and histopathological examination findings for resected valve specimens was examined. When valves were removed before the end of treatment, organisms were seen on the Gram stain of ground valve material performed in the microbiology laboratory and on Gram-stained histopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 32 publications
3
48
1
9
Order By: Relevance
“…Gram stain of tissue processed in the microbiology laboratory may be more sensitive than histopathological Gram stain of tissue sections, 81% versus 67% in one study; however, in 10% of cases, the histopathology Gram stain detected organisms while the microbiology Gram stain was negative (17). Unfortunately, several studies have shown that culture of valve tissue suffers from low sensitivity and specificity, with positive cultures in only 6% to 26% of endocarditis cases (17,18,25). A microorganism different from that identified by blood culture or valve PCR was detected in 36% (10/28) of positive valve cultures in one study, suggesting a high rate of false positivity of valve culture (25).…”
Section: Evaluation Of Excised Cardiac Valvular Tissuementioning
confidence: 81%
See 3 more Smart Citations
“…Gram stain of tissue processed in the microbiology laboratory may be more sensitive than histopathological Gram stain of tissue sections, 81% versus 67% in one study; however, in 10% of cases, the histopathology Gram stain detected organisms while the microbiology Gram stain was negative (17). Unfortunately, several studies have shown that culture of valve tissue suffers from low sensitivity and specificity, with positive cultures in only 6% to 26% of endocarditis cases (17,18,25). A microorganism different from that identified by blood culture or valve PCR was detected in 36% (10/28) of positive valve cultures in one study, suggesting a high rate of false positivity of valve culture (25).…”
Section: Evaluation Of Excised Cardiac Valvular Tissuementioning
confidence: 81%
“…Current recommendations for the diagnosis of endocarditis also recommend culture of valvular tissue, with culture results being used to direct the duration of postoperative antimicrobial therapy (1,6,9). Gram stain of tissue processed in the microbiology laboratory may be more sensitive than histopathological Gram stain of tissue sections, 81% versus 67% in one study; however, in 10% of cases, the histopathology Gram stain detected organisms while the microbiology Gram stain was negative (17). Unfortunately, several studies have shown that culture of valve tissue suffers from low sensitivity and specificity, with positive cultures in only 6% to 26% of endocarditis cases (17,18,25).…”
Section: Evaluation Of Excised Cardiac Valvular Tissuementioning
confidence: 97%
See 2 more Smart Citations
“…In a recent study, the presence of histological signs of infective endocarditis (IE) correlated with the presence of bacterial DNA in heart valve tissue, and when patients had no histological evidence of IE, PCR amplification was always negative (10). A recent study has shown that the presence of Gramstaining organisms in heart valves of patients cured of IE does not predict the presence of viable organisms (29). However, it has not been determined whether DNA amplification from valve tissue is predictive of an active infectious process.…”
mentioning
confidence: 99%